Evaluation of the NFHS Online Captains Leadership Course: Student Athletes’ Views of Effectiveness - Walker, Lauren F.; Gould, Daniel R. (Frontiers in Psychology, 2021)
Sport is viewed as an arena for positive life skill development, including leadership development. In 2015, the NFHS launched an online Captain’s Leadership Training Course. The main purpose of this study was to examine the effectiveness of the course in improving leadership knowledge and ability. An electronic survey was sent to a sample of athletes (n = 202, 129 female), ages 13-19 (M = 17.01, SD = .10) in eight U.S. states who had completed the NFHS course within the last 3-18 months. Most athletes (92.6%) completed the course based upon their coach’s recommendation. The course was viewed to be moderately to very useful (M = 2.49, SD = 1.00) in helping them in preparing to be a team captain. Participants believed the course to be very to extremely effective in building their knowledge on motivation (M = 1.96, SD = .89), communication (M = 1.90, SD = .80), decision making (M = 2.03, SD = .91), peer modeling (M = 1.91, SD = .86), team cohesion (M = 1.96, SD = .88) and problem solving strategies (M = 2.00, SD = .85). Canonical correlation analyses showed that athletes who felt they were more reflective tended to rate the effectiveness of the course lower than their peers. Additionally, analyses did not show any clear demographic characteristics that distinguished between perceptions of the effectiveness of the course, showing the value found in the course was high with all types of scholastic athletes. Athletes felt the course could be improved most in the area of learning how to manage conflict with their peers and coaches. Future research in scholastic leadership should seek to understand the impact of the course prospectively across a high school sport season.